2010
DOI: 10.1128/jvi.00374-10
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Resistance to CCR5 Antagonists Associated with Highly Efficient Use of CCR5 and Altered Tropism on Primary CD4 + T Cells

Abstract: We previously reported on a panel of HIV-1 clade B envelope (Env) proteins isolated from a patient treated with the CCR5 antagonist aplaviroc (APL) that were drug resistant. These Envs used the APL-bound conformation of CCR5, were cross resistant to other small-molecule CCR5 antagonists, and were isolated from the patient's pretreatment viral quasispecies as well as after therapy. We analyzed viral and host determinants of resistance and their effects on viral tropism on primary CD4 ؉ T cells. The V3 loop cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
67
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 56 publications
11
67
1
Order By: Relevance
“…Late fusion events occur at similar rates in different viral isolates, so it is likely that the differences we observed in entry kinetics reflect changes in the kinetics of binding to CD4, CCR5, or both (29). Increased coreceptor affinity accelerates viral fusion; because CCR5 antagonist-resistant HIV-1 uses the drug-bound CCR5, the V3 loop mutations that confer resistance must increase gp120 affinity for the antagonist-coreceptor complex (36,40,44,54,59). A clonal analysis of env sequences from Sub07 and Sub57, however, demonstrated that even after the virus acquired the capacity to use the drug-coreceptor complex, resistance mutations continued to accumulate.…”
Section: Discussionmentioning
confidence: 99%
“…Late fusion events occur at similar rates in different viral isolates, so it is likely that the differences we observed in entry kinetics reflect changes in the kinetics of binding to CD4, CCR5, or both (29). Increased coreceptor affinity accelerates viral fusion; because CCR5 antagonist-resistant HIV-1 uses the drug-bound CCR5, the V3 loop mutations that confer resistance must increase gp120 affinity for the antagonist-coreceptor complex (36,40,44,54,59). A clonal analysis of env sequences from Sub07 and Sub57, however, demonstrated that even after the virus acquired the capacity to use the drug-coreceptor complex, resistance mutations continued to accumulate.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 resistance to such inhibitors is likely to entail unique escape mechanisms given that a host receptor, not a viral enzyme, is the drug target. Potential pathways of resistance to these inhibitors include coreceptor switching to CXCR4-using viruses (16), increased affinity and binding to CD4 and/or CCR5 (17,18), use of inhibitorbound conformations of CCR5 (19,20), and increased kinetics of membrane fusion (21). Although outgrowth of CXCR4-using virus remains a concern for the therapeutic administration of CCR5 antagonists and is why patients are screened for X4-tropic virus prior to starting a maraviroc regimen, de novo mutations altering coreceptor tropism do not appear to be the preferential pathway for resistance (22,23).…”
mentioning
confidence: 99%
“…Because of down regulation of CD4 by HIV-1, cells actively producing virus are seen as CD4/CD8 double-negative T cells (Kaiser et al 2007). In cell culture HIV-1 infects activated cells with much greater efficiency than quiescent cells (Korin and Zack 1998), with central and effector memory cells as the primary targets (Pfaff et al 2010). However, in vivo there appears to be a type of CD4 þ T cell that does not express surface activation markers but supports significant levels of infection, particularly in the gut mucosa (Veazey et al 2000;Brenchley et al 2004b;Li et al 2005;Mattapallil et al 2005;Mehandru et al 2007).…”
Section: Target Cells T-cell Subsetsmentioning
confidence: 99%